Mathematical model for prediction of maximum force in leg press 45° in adult men - de Souza Junior, J. J.; Gurgel de Alencar Carvalho, M. C.; Borba-Pinheiro, C. J.; Braga de Mello, D.; Minelli Rodrigues, B.; Dantas, E. H. M. (Brazilian Journal of Biomotricity, 2011)
Mathematical model for prediction of maximum force in leg press 45o in adult men. Brazilian Journal of Biomotricity, v. 5, n. 1, p. 53-63, 2011. This study aimed to develop a mathematical model to predict maximal muscle strength for the 45o leg press exercise. 98 apparently healthy and trained men have voluntarily participated in this study composing two randomized groups: learning sample (GA, n = 51, 21.8+3.6 years) and test group (GT, n = 47, 22+3.3 years). Test was performed one repetition maximum (1RM) 45 o Leg Press exercise. Anthropometric measurements were taken and body composition parameters were calculated. The predictor mathematical model were calculated through Backward Stepwise Solution method, accepting p < 0.05. The model presented r = 0.78; r2(multiple) = 0.61, r2(adjusted) = 0.53 and p = 0.00001, for height, BMI, thigh girth, thigh length, femur breadth, fat %, LBM and fat mass variables. These parameters were all significant (p < 0.05). The results may infer that this model may be applied to estimate 1RM for Leg Press 45o in trained between 18 and 30 years.